Comparison Between Traditional Time Series Forecasting Models: An applied Study for Primary Schools Students- Iraq/ Karbala Governorate Students as a Sample - Daham Owaid Matrood (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Education is a prerequisite for improving the standard of living, empowering women, protecting children from the harsh effects of child labor and sexual violence, supporting human rights and democracy, protecting the environment. In addition, the education is guiding population growth universal access to primary education for the world's children is one of the Millennium Development Goals (MDG’S) Objectives of “A World Fit for Children” (WFFC). The discrepancy in the quality of the estimated regression models and the inability to use some of them because they do not have the characteristics of good estimators, which leads to a lack of confidence in their predictive or estimation accuracy. The research aims to estimate the general trend regression models using the ordinary least squares method and compare the results of the estimation using the differentiation criteria (AIC, BIC, MSE) and to determine the optimal model as well as to predict the number of primary students in the holy province of Karbala for the time period (2022-2028). The researcher found the best suitable model for prediction, which is the general linear trend model, table 4, which represents the predictive values ​​of primary students.